(untitled) (Communications in Computational Physics, 2010)
A boundary condition-enforced immersed boundary-lattice Boltzmann method (IB-LBM) for the simulation of particulate flows is presented in this paper. In general, the immersed boundary method (IBM) utilizes a discrete set of force density to represent the effect of boundary. In the conventional IB-LBM, such force density is pre-determined, which cannot guarantee exact satisfaction of non-slip boundary condition. In this study, the force density is transferred to the unknown velocity correction which is determined by enforcing the non-slip boundary condition. For the particulate flows, accurate calculation of hydrodynamic force exerted on the boundary of particles is of great importance as it controls the motion of particles. The capability of present method for particulate flows is depicted by simulating migration of one particle in a simple shear flow and sedimentation of one particle in a box and two particles in a channel. The expected phenomena and numerical results are achieved. In addition, particle suspension in a 2D symmetric stenotic artery is also simulated.